Effects of Structured Play Interventions on Self-Esteem, Physical Competence, and Psychological Well-Being in Children - Molodanova, Anastasia; Zaborova , Victoria; Budanova , Elena; Dana, Amir (Health Nexus, 2026)
AbstractStructured play has been proposed as an effective approach to enhance both physical and psychological health in children; however, evidence from school-based interventions examining self-esteem, perceived physical competence, and psychological well-being simultaneously remains limited. This study examined the effects of an eight-week structured play intervention on self-esteem, perceived physical competence, and psychological well-being in children aged 8–11 years. In this quasi-experimental pretest–posttest study, 68 children were recruited from primary schools in Tehran, Iran, and conveniently allocated to a structured play intervention group (n = 34) or a control group (n = 34). The intervention comprised two 45-minute sessions per week for 8 weeks, including skill-based activities, cooperative games, and reflection periods. Outcomes were assessed using the Rosenberg Self-Esteem Scale (child-adapted), the Physical Self-Perception Profile for Children, and the KIDSCREEN-27 (total score). Pre- and post-intervention data were analyzed using ANCOVA, controlling for baseline scores, with effect sizes reported as partial eta squared (η²p). The results revealed significant intervention effects on all outcomes. Self-esteem improved significantly in the intervention group compared with controls (F(1, 65) = 18.42, p < 0.001, η²p = 0.22). Similarly, perceived physical competence (F(1, 65) = 32.15, p < 0.001, η²p = 0.33) and psychological well-being (F(1, 65) = 24.87, p < 0.001, η²p = 0.28) increased significantly. Paired-sample t-tests confirmed pre- to post-intervention improvements in the intervention group (all p < 0.001), whereas changes in the control group were non-significant. An 8-week structured play program delivered in schools was associated with meaningful improvements in self-esteem, perceived physical competence, and psychological well-being in children aged 8–11 years, supporting its potential for promoting holistic development in educational and community settings.Keywords: Structured play; School-based intervention; Self-esteem; Physical competence; Psychological well-being; Children